VIRUS ABORTION OF MARES - ΣΕΪΤΑΡΙΔΗΣ Κ.; ΡΑΝΤΣΙΟΣ Α.; ΤΣΑΓΓΑΡΗΣ Θ.; ΟΜΗΡΟΣ Α. (Journal of the Hellenic Veterinary Medical Society, 1974)
A case of virus abortion in mares is described. The diagnosis is based upon the presence of eosinophilinic inclusions in the bronchial epithelium and the hepatic cells as well as in the presence of Herpes virus antibodies. The mares which gave birth to which died alter a few to 96 hours with central nervous system symptoms (excitation - depression) have had a normal pregnancy (333, 75 ± 2,31 days). The mares were presenting also symptoms of vesicular coital exanthema